2020
DOI: 10.18203/2320-1770.ijrcog20203322
|View full text |Cite
|
Sign up to set email alerts
|

A study to compare acceptability, safety and continuation rates of combined hormonal pill and centchroman as post abortion contraceptives

Abstract: Background: Centchroman a non-steroidal selective estrogen receptor modifier (SERM). It is highly effective contraceptive which is devoid of side effects of COCs and there is prompt return of fertility upon discontinuation. Data in terms of its acceptability and continuation rates is limited when compared to combined oral contraceptive (COC). Therefore, the study was planned to study the acceptability, efficacy and continuation rates of centchroman and compare it with the combined oral contraceptives.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Almost 33% of married women of reproductive age in India do not use any methods of contraception [1]. Postpartum contraception is an effective method for ensuring adequate contraception coverage and reducing unmet needs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Almost 33% of married women of reproductive age in India do not use any methods of contraception [1]. Postpartum contraception is an effective method for ensuring adequate contraception coverage and reducing unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…Centchroman was introduced into the family planning basket of contraceptives but is underutilised as a postpartum spacing method despite its safety and convenient dosing schedule. Recent studies have demonstrated that centchroman has higher satisfaction and continuation rates than postpartum intrauterine devices and progesterone-only pills [1,4]. No untoward side effects have been reported with centchroman use till now [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations